GPS receiver code bias estimation: A comparison of two methods. Issue 8 (15th April 2017) - McCaffrey, Anthony M.; Jayachandran, P.T.; Themens, D.R.; Langley, R.B.
Highlights: Using co-located GPS receivers, the CODE provided receiver biases were found to be accurate within 0.742 TECU. With the same technique, the Minimization of Standard Deviations method was found to be accurate within 1.472 TECU. The Wettzell stations were shown to have a multipath issue, displaying unexpected variations in TEC through all arcs. Abstract: The Global Positioning System (GPS) is a valuable tool in the measurement and monitoring of ionospheric total electron content (TEC). To obtain accurate GPS-derived TEC, satellite and receiver hardware biases, known as differential code biases (DCBs), must be estimated and removed. The Center for Orbit Determination in Europe (CODE) provides monthly averages of receiver DCBs for a significant number of stations in the International Global Navigation Satellite Systems Service (IGS) network. A comparison of the monthly receiver DCBs provided by CODE with DCBs estimated using the minimization of standard deviations (MSD) method on both daily and monthly time intervals, is presented. Calibrated TEC obtained using CODE-derived DCBs, is accurate to within 0.74 TEC units (TECU) in differenced slant TEC (sTEC), while calibrated sTEC using MSD-derived DCBs results in an accuracy of 1.48 TECU.